The impact of union of European Football Associations (UEFA) financial fair play regulation on audit fees: Evidence from Spanish football - Mercedes Mareque; Angel Barajas; Francisco Lopez-Corrales (International Journal of Financial Studies, 2018)
This paper analyzes whether the Financial Fair Play (FFP) regulations set by Union of European Football Associations (UEFA) have influenced the auditing fees charged to football clubs. In addition, it explores the determinants of audit fees. We used a two-sample t-test with equal variances to determine whether differences are present. After this, we carried out a panel data regression with the clubs fix effect to estimate the determinants of audit fees in football clubs. Our findings revealed an increase of audit fees after the implementation of FFP regulations. On top of that, audit fees were explained by the presence of foreign investors if the audit firm was one of the Big 4 and if the auditor was a woman. The regulation change has had an impact on the audit fees charged by auditors for their services. However, this increase may be compensated over future years given the improving financial situation of clubs; therefore, the auditors' risk diminishes and subsequent audit fees may be reduced. UEFA should monitor audit fees as well as the quality of the audit reports, which have become crucial to obtaining the license to participate in UEFA competitions.
Keywords: Z2; M41; M42; 330; dividend; football; audit fees; audit shopping; Financial Fair Play; UEFA